PENGARUH BAKTERI PENGOLAH LIMBAH ORGANIK PALBA TERHADAP KARAKTERISTIK AIR LINDI YANG DIHASILKAN PADA TIMBUNAN SAMPAH DI TEMPAT PENGOLAHAN AKHIR SAMPAH (TPAS) SISTEM OPEN DUMPING DAN SANITARY LANDFILL - , RYNA TAMBUNAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bacteria Palba was a group of organic waste processing bacteria that consists of::l::70 species of symbiotic bacteria and fungi that decomposed complex organic materials into simpler form. The objective of the research were to determine the effect of bacterial processing of organic waste Palba in forming the characteristics of leachate generated at the end of processing waste in final disposal (TPAS) by using system open dumping and sanitary landfill and to obtain an optimal dose of bacteria Palba given in the landfiJl waste that can reduce levels of pollutants most optimal. The Research executed by chopping the waste first and mixed so that it becomes a homogeneous waste, then waste is divided into two parts, namely the reactor with open dumping system and reactor with sanitary landfill system. Each reactor or TPAS model is subdivided according to a given dose of bacteria Palba i.e. 0 mI, 0.125 mI, 0.25 mI, 0.5 ml, 0.75 mI and 1 mI. The dose of bacteria is given once, then the waste watered as much as 300 ml per day. On each day m~urements were taken for the temperature of solids, room temperature and quantity of leachate generated. Measurements of pH, leachate levels of pollutants contained in the leachate are: TSS, TDS, COD, BOD, NH3-N were taken every 3 days.Then the observations of Palba bacterial growth at 20Â°C and 37 Â°c temperature also done during the process of research. From conducted research, Palba bacteria only known that can affect the BOD in the leachate generated from the reactor with open dumping system, while the other parameters such as TSS, IDS, COD and NH3-N is not there a significant difference in the presence of bacteria Palba usage. While the system sanitary landfill reactor, all parameters (TSS, IDS, COD, BOD and NH3-N) showed no difference at all. So it can be said that the use of bacteria can degrade BOD Palba leachate generated in the open dumping system reactor with a dose of bacteria 0.25 mJ per 8.3 kg of waste. Thus, bacteria dose in the TPAS if scaled up, it becomes every one waste truck with a capacity of 3.5 tons, it is advisable to spray bacteria Palba as much as 0.1 liters.